FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BEROBAT MASYARAKT GAMPING KE PUSKESMAS - Agus Warseno (MEDIA ILMU KESEHATAN, 2013)
Background: Community Health Center Gamping II is a community-based health care unit where Showed an increased number of visit or severy day. On the other hand, the increasing private health care facilities around the Gamping community environment may affect the public interest toutilize medical services at the health center . Objective:Knowing the factors that affect the interests of the Gamping’s people treatedat the health center Gamping II . Method:This study is a cross-sectional survey.This study is non-experimental research (observation with out intervention) with survey located in the regionof Gamping. Subjects were people who in the last 6 months sick and need treatment .Determination sample with sistematic random sampling, 74 samples obtained from the 299 number. Retrieval of data using question naires. The data analys is was done by quantitative descriptive and statistical regression test . Results: This study found that community service is desired to haveacle an environment , providefriendly service, strategic location and easy to reach, complete drug inventory, easy toconsult withadoctor. Subjective norm is mainly influenced by parents, family members/relatives, friends and doctors/healthworkers. Quantitative data analysis with multiple regression statistical test showednoeffect oftheweakagainst the interestsof theactual behavior of treatment (p=0.044and r =0.221), there was no effect of attitudes toward interest treatment (p=0.325 and r =-0.094), there was no influence of subjective norm to intention treatment (p=0.081 and r =0.217), therewasnoeffect together thanactual behavior, attitudes,subjectivenorms to intention treatment (p=0.072). Conclusion: Basedon this research can beconcluded that theactual behavioral factors have aweak influence on the treatment interest,attitude does not affect the interest of treatment and subjective norm is not having an effect on the interest . Keywords: Actual behavior, attitudes, subjective norms, interest in treatment, Community health center